2015
DOI: 10.1016/j.apjtm.2015.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic and antioxidant activities of Nypa fruticans Wurmb. vinegar sample from Malaysia

Abstract: Aqueous extract of NPV possesses antihyperglycaemic activities comparable to the metformin, while the ethyl acetate extract precipitated significant antioxidant effects attributable to its high phenolic content. These findings suggest that antioxidant compounds of NPV do not contribute much towards the overall observed antidiabetic effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(33 citation statements)
references
References 25 publications
1
30
0
2
Order By: Relevance
“…At a concentration of 100 mg/mL, N. fruticans extract could inhibit the growth of E. coli and S. aureus but not that of the fungus C. albicans (Table 2). Yusoff et al (2015) reported the ethyl acetate-soluble part of N. fruticans showed a potent antioxidant activity whereas the water extract was able to improve blood sugar levels in streptozotocin-induced diabetic rats.…”
Section: Resultsmentioning
confidence: 99%
“…At a concentration of 100 mg/mL, N. fruticans extract could inhibit the growth of E. coli and S. aureus but not that of the fungus C. albicans (Table 2). Yusoff et al (2015) reported the ethyl acetate-soluble part of N. fruticans showed a potent antioxidant activity whereas the water extract was able to improve blood sugar levels in streptozotocin-induced diabetic rats.…”
Section: Resultsmentioning
confidence: 99%
“…vinegar and described mechanisms that led to inhibition of glucose transporters 19 . Similarly, these authors showed anti-diabetic and anti-oxidant properties of this Malaysian vinegar, but did not identify or isolate active ingredients 18 .…”
Section: Discussionmentioning
confidence: 99%
“…The effect of different extract in alloxan induced diabetic rats was found to be significant when compared with standard drug glibenclamide. 29 Wertia corymbosa (Grieb. )…”
Section: Anthocleista Vogelii (Planc)mentioning
confidence: 99%